Pertanggungjawaban Pidana Beneficial Owner dalam Kejahatan Korporasi di Bidang Sumber Daya Alam - As’ad Imam Muhtadi; Arvina Hafidzah; Dominikus Rato; Fendi Setyawan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This article focuses on the criminal liability of beneficial owners for crimes in the natural resources sector. By using legal research methods, through statutory and conceptual approaches, there are three discussions in this article, first is that a BO can be directly included in the structure of the corporation cannot directly have a position and is only bound by only through relationships or affiliations. Second, the concept of criminal liability for BOs in Indonesia has not yet been formulated with certainty, so it cannot create a sense of obligation for BOs. And, ideal forms of accountability are collaboration between the theories of strict liability and direct corporate criminal liability. Corporations in their accountability don’t abdicate responsibility from management who commit criminal acts. Linked to BO as a corporate controller outside the structure, they can also be held accountable accordance to corporate responsibility paradigm changes in the 2023 Criminal Code.